Answer: x
=
6
Explanation:
the initial statement is
x
∝
1
y
to convert to an equation multiply by k the constant
of variation
⇒
x
=
k
×
1
y
=
k
y
to find k use the given condition
x
=
4
when
y
=
9
x
=
k
y
⇒
k
=
x
y
=
4
×
9
=
36
equation is
¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯
∣
∣
∣
2
2
x
=
36
y
2
2
∣
∣
∣
−−−−−−−−−−−−
when
y
=
6
then
x
=
36
6
=
6
Step-by-step explanation:
Answer:
use the mixed fraction mathsoup calculator, it shows step by step, im just trying to help
Step-by-step explanation:
hope i helped:)
Answer:
Step-by-step explanation:
1st one
<span>Simplifying:
2x2 + -8x + -90 = 0
Reorder the terms:
-90 + -8x + 2x2 = 0
Solving
-90 + -8x + 2x2 = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), '2'.
2(-45 + -4x + x2) = 0
Factor a trinomial.
2((-5 + -1x)(9 + -1x)) = 0
Ignore the factor 2.
Subproblem 1:
Set the factor '(-5 + -1x)' equal to zero and attempt to solve:
Simplifying
-5 + -1x = 0
Solving
-5 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '5' to each side of the equation.
-5 + 5 + -1x = 0 + 5
Combine like terms:
-5 + 5 = 0
0 + -1x = 0 + 5
-1x = 0 + 5
Combine like terms:
0 + 5 = 5
-1x = 5
Divide each side by '-1'.
x = -5
Simplifying
x = -5
Subproblem 2:
Set the factor '(9 + -1x)' equal to zero and attempt to solve:
Simplifying
9 + -1x = 0
Solving
9 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-9' to each side of the equation.
9 + -9 + -1x = 0 + -9
Combine like terms:
9 + -9 = 0
0 + -1x = 0 + -9
-1x = 0 + -9
Combine like terms:
0 + -9 = -9
-1x = -9
Divide each side by '-1'.
x = 9
Simplifying
x = 9
Solution
x = {-5, 9}</span>